The Effect of Leadership Style, Trust, and Work Ethic as Mediation on The Work Engagement of AI's Companies - Sihite, Otto Berman; Sinaga, Poltak; Bernarto, innocentius; Sijabat, Rosdiana (Esensi: Jurnal Bisnis dan Manajemen, 2021)
The objective of the research purpose is to analyze if there is an effect of the Leadership Style, Trust, and Work Ethic, towards Engagement especially to the service department. Due to the fact that complaints increased from customer and impact to less satisfactory. A quantitative approach, with path analysis, and survey research designs using a questionnaire used to test hypotheses for employees in the service section from the labor level to the Supervisor position. Total samples 78 people taken from 100 populations. It was discovered from the results, that work ethic has a positive and important influence on working engagement that decrease the level complaints, which makes this research special since no related research has been done so far.Cara Mengutip:Sihite, O. B., Sinaga, P., Bernarto, I., & Sijabat, R.. (2021). The Effect of Leadership Style, Trust, and Work Ethic as Mediation on The Work Engagement of AI's Companies. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.20247.